Pengembangan Media Jaring-Jaring Bangun Ruang Dalam Model Pembelajaran Assure Kelas V Semester II di SDN Pucang Sidoarjo - Eny Wahyudati (Universitas PGRI Adi Buana Surabaya, 2017)
Media Development Research Jaring-jaring Bangun Ruang with ASSURE Learning Model Class V Semester II SDN Pucang Sidoarjo district motivated by learning according to the observations of researchers are still teacher-centered. Task of the teacher explains the subject matter, giving example problems and exercises, while the assignment of students just listen to the teacher's explanations, noting the subject matter and do the exercises. Because of lack of varied learning, then students easily saturated and bored. The purpose of this development is to produce research of learning nets Media Room Wake up to the steps of learning ASSURE Learning Model is expected to improve the quality of learning. ASSURE Learning Model is done with these steps: Analyse learner, State objectives, Select methods, media, materials, utilize media and materials, Require learner participation, and Evaluate and revise. ASSURE learning activities include: 1) identify and analyze the characteristics of students associated with learning outcomes, 2) formulate and set learning goals, 3) choosing a strategy, choosing technologies and media as well as modify the material, 4) teacher planning to use the technology, media and materials to achieve learning goals, 5) learning requires active mental engagement of students, 6) tested the learning process, assess and revise the material. After students learn with media Jaring-jaring Bangun Ruang in the ASSURE Learning Model in which students more effective learning activities, students find pleasure in learning and achievement. This is evident with the increase in the acquisition of learning. Increased learning ability is supported by student work in the form of worksheets and observation of student activity sheets. Also from the questionnaire responses of students towards learning it, obtained an average score of 10 item statements given is 88.3 This shows that the response of students towards learning nets to Build Space ASSURE Learning Model can be very positive category. Based on the findings of this study, it is recommended to teachers of mathematics in making learning as follows: (1) makes the ASSURE Learning Model as a liberation ¬ lesson worth considering alternatives, (2) assist students in learning through the use of modern media, (3) develop this study that the results of this study is more comprehensive and profound.